The small boxy/peanut structure of the Milky Way traced by old stars - Semczuk, Marcin; Dehnen, Walter; Schönrich, Ralph; Athanassoula, Evangélie (Monthly notices of the Royal Astronomical Society, 2022)
We analyse the positions of RR Lyrae stars in the central region of the Milky Way. In addition to the overall bar shape detected previously, we find evidence for a peanut shaped structure, in form of overdensities near ℓ = −2 and 1° at b ∼ −3.5°. The corresponding physical distance between the two peaks of the peanut is $\sim 0.7\,$ kpc, significantly shorter than that found from near-IR images (3.3 kpc) and red-clump stars. Qualitatively this is expected from ‘fractionation’ of bar orbits, which we demonstrate to be matched in a simulation of an inside-out growing disc subsequently forming a bar.
Advance access publication 2021 November 13
Gesehen am 23.03.2022